2024
DOI: 10.3390/app14093575
|View full text |Cite
|
Sign up to set email alerts
|

Synergies and Potential of Industry 4.0 and Automated Vehicles in Smart City Infrastructure

Michal Kaššaj,
Tomáš Peráček

Abstract: The integration of Industry 4.0 and automated vehicles into the smart cities concept is a topical issue in the urbanization of cities and technological innovation within cities. As it is a relatively modern issue, many aspects of this field have not yet been explored; as a consequence, this paper is concerned with the search for synergies between Industry 4.0 and automated vehicles in smart city infrastructures. There is a lack of contributions in this field that summarize these synergies in a single article a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The current literature suggests that, while perceived privacy is important in all regional and cultural contexts, it is especially important in a smart sustainable city context, where users tend to have lower levels of experience with emerging (smart sustainable) technologies [100], and in cultures where socio-religious values have a strong impact on individual attitudes and behaviours [101]. Perceived privacy is therefore critical to acceptance and adoption [102][103][104]. It is thus intuitively reasonable to suppose that higher levels of perceived privacy lead to higher intention to use CIT.…”
Section: Research Model Development and Hypothesesmentioning
confidence: 99%
“…The current literature suggests that, while perceived privacy is important in all regional and cultural contexts, it is especially important in a smart sustainable city context, where users tend to have lower levels of experience with emerging (smart sustainable) technologies [100], and in cultures where socio-religious values have a strong impact on individual attitudes and behaviours [101]. Perceived privacy is therefore critical to acceptance and adoption [102][103][104]. It is thus intuitively reasonable to suppose that higher levels of perceived privacy lead to higher intention to use CIT.…”
Section: Research Model Development and Hypothesesmentioning
confidence: 99%
“…From a micro perspective, green finance can not only strengthen the supervision and management of fund utilization by financial institutions but also enhance their own environmental responsibility efficiency. Research has shown that green finance does indeed have a promoting effect on ecological environment protection [19][20][21][22]. On the one hand, green finance can promote ecological environment protection through the allocation of financial resources [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Tunisia embarked on e-administration in the 1990s to modernize its administrative systems and has recently focused on generalizing e-services and establishing frameworks for e-government achievements [50][51][52][53]. Similarly, in December 2006, Bahrain announced plans to initiate e-government in the Gulf, aiming to enhance online services through various channels including portals and mobile devices [54][55][56][57]. Jordan, Egypt, and Oman have also made significant strides in integrating ICT with government services to enhance efficiency, participation, and transparency, which are essential for fostering a competitive, robust, and knowledge-based economy [57][58][59].…”
mentioning
confidence: 99%